2006
DOI: 10.2527/2006.843588x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of chronic stress and social status on various physiological and performance measures in pigs of different breeds1

Abstract: Pigs typically experience various environmental stressors, which can negatively affect performance. Cortisol concentrations and various immune and performance measures are influenced by breed, but few data exist describing the impact of breed on stress responsiveness in pigs. The objective of this experiment was to determine if certain physiological responses to chronic stressors differed among 3 breeds and 2 commercial lines of pigs. The pigs were Landrace (n = 36), Meishan (n = 30), Yorkshire (n = 32), or 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
88
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 28 publications
6
88
1
5
Order By: Relevance
“…This is corroborated by the finding that the larger the pigs' adrenal cortices were, the lower their salivary cortisol levels tended to be. Sutherland et al (2006) found that 7-week-old pigs exposed to multiple concurrent stressors (mixing, crowding and heat stress of 33 6 58C) for 14 days had significantly lower plasma cortisol concentrations when measured at both 7 and 14 days after the onset of these conditions. Lower salivary cortisol levels are often observed under conditions of chronic stress and can be attributed to the dynamics of the HPA response; cortisol levels are elevated shortly after the axis is activated, but eventually a counter-regulatory response can lead to circulating cortisol concentrations below that of pre-stress levels (Miller et al, 2007).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This is corroborated by the finding that the larger the pigs' adrenal cortices were, the lower their salivary cortisol levels tended to be. Sutherland et al (2006) found that 7-week-old pigs exposed to multiple concurrent stressors (mixing, crowding and heat stress of 33 6 58C) for 14 days had significantly lower plasma cortisol concentrations when measured at both 7 and 14 days after the onset of these conditions. Lower salivary cortisol levels are often observed under conditions of chronic stress and can be attributed to the dynamics of the HPA response; cortisol levels are elevated shortly after the axis is activated, but eventually a counter-regulatory response can lead to circulating cortisol concentrations below that of pre-stress levels (Miller et al, 2007).…”
Section: Discussionmentioning
confidence: 87%
“…Production parameters of weight gain, food conversion efficiency and back fat were recorded as a strong link between chronic stress and poor growth performance is frequently observed (e.g. Hyun et al, 1998;Sutherland et al, 2006;Foury et al, 2007). One of the key causal mechanisms of this relationship is thought to be the general catabolic influence of high circulating cortisol on certain muscle types and fat cells (Sapolsky et al, 2000;Yoshioka et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although many stressors have been reported to increase plasma cortisol concentrations in pigs (Becker et al, 1985;Parrott and Misson, 1989), conflicting results have been reported by other researchers. For example, lower cortisol levels were detected in heat-stressed pigs compared with coldstressed and transportation-stressed pigs, with statistically similar values for cortisol compared with control pigs (Hicks et al, 1998, Sutherland et al, 2006. Furthermore, heat stress did not increase plasma cortisol in cows with the exception of a slight elevation on the first day of heat stress (Farooq et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal separation, relocation, introduction to new social groups, the establishment of social dominance and a change in diet to a higher dry mass content induce physiological changes in recently weaned swine, with a consequent reduction in weight gain being observed (Sutherland et al 2006, Kojima et al 2008. These alterations lead to increased cortisol serum levels (Heo et al 2003) and possible effects on the immune response of animals (Bonnette et al 1990), such as a reduction in neutrophil microbicidal capacity and reduced function of natural killer cells and lymphocytes (Sutherland et al 2006, Da Costa et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…These alterations lead to increased cortisol serum levels (Heo et al 2003) and possible effects on the immune response of animals (Bonnette et al 1990), such as a reduction in neutrophil microbicidal capacity and reduced function of natural killer cells and lymphocytes (Sutherland et al 2006, Da Costa et al 2008. Metz and Gonyou (1990) observed that the immune system of swine weaned at four weeks of age is not yet fully developed.…”
Section: Introductionmentioning
confidence: 99%